Konsep Alkitab 2 Timotius 2:1-10 Tentang Penganiayaan/Penderitaan - Tobi, Ongki Riando; Dju, Oktavia Adevin; Harming, Harming (Jurnal Teologi Praktika, 2024)
Bible Concept, 2 Timothy 2:1-10, Persecution. Every human being has certainly suffered suffering. Each person has their own way of looking at the meaning of suffering. Christianity believes that God's purpose in creating humans was not to suffer. Paul in 2 Timothy 3:12 reminds and reaffirms to believers that everyone who wants to live a godly life in Christ Jesus will suffer suffering. Some of the people who suffered for the truth were Job, Jeremiah, Jesus Christ, Stephen, the Apostle Paul. The cause of human suffering is doing God's work, and on the other hand it is also caused by sin, nature, disease. But believers respond by believing that everything aims to become stronger in Christ, suffering as soldiers, God gives understanding in everything, truth cannot be shackled, behind suffering because of the Gospel there is a soul that saves. The sufferings that exist lead us to join in and suffer together with Christ and have enthusiasm in the work of preaching the Gospel and remain strong and steadfast in the midst of the storm.